History curricula for national reconciliation: An analysis of history textbooks in secondary schools in Sri Lanka - Nanayakkara, N.I. (University of Colombo, 2017)
The concept of national reconciliation has become a key concern in post-war Sri Lanka. The government of Sri Lanka has been trying to build a nation within a framework of multi-culturalism during and after the war. As a long-term policy, the education system plays a vital role in building social cohesion. The first report of the National Education Commission has established the achievement of a functioning sense of national cohesion, national integrity, and national unity (Report of the NEC, 1992). Nevertheless, the history textbooks in Sri Lanka, containing historical narratives which shape and mould the historical consciousness of the Sinhala and Tamil communities, pose a fundamental challenge to the process of national reconciliation. Much research done overseas (on the history textbooks in Rwanda, Israel, and so on) has proven how history textbooks can highlight social, cultural, and ethnic diversity and promote mutual respect and tolerance among different ethnic groups. This study examines the contribution of history textbooks to reconciliation by analysing the historical narratives in them. The aim of the study is to develop a theoretical discussion on the gap between national reconciliation and history textbooks in Sri Lanka. The research method is mainly qualitative data collection through library research. A content analysis was used for Sinhala-medium history textbooks from grade six to grade eleven. The analysis of the textbooks with the use of the theoretical concepts of historical significance, memorialization, and racial hierarchy show that the historical narratives in the textbooks are full of omissions. These textbooks provide Sinhala-centric narratives which have omitted the Tamils and Muslims in the country. The textbooks are highly ideologised, and they portray the Sinhala kings as heroes defeating the Tamils. To construct a sober dialogue between the Sinhalese and Tamils, it is essential to transform narratives based on a single point of view to alternative views, such as a shared history or joint history.
Keywords: national reconciliation, history text books, historiography, historical significance, shared history